Place of Women in Sri Lankan Society: Measures for Their Empowerment for Development and Good Governance - Herath, H.M.A. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2015)
Despite far-reaching economic, social and political developments in Sri Lanka over the last century or so, Sri Lankan women continue to occupy a subordinate status. While women are not subjected to extreme forms of oppression, many adverse structures and forces, such as the patriarchal social structure, woman’s role in the family, traditional values, rituals and myths, the division of labour and unequal pay, and women’s lack of participation in politics contribute to the continuing subordination of Sri Lankan women. In this context, this article seeks to address the socio-economic, cultural and political processes that shape the status and the progress of women in Sri Lanka. It emphasizes the policy makers to ensure that Sri Lankan women are empowered to participate in development. For this to happen, the article, however, argues that an attitudinal change and a paradigm shift in the minds of policy makers and the society at large must be accomplished.
Keywords: Empowerment, Sri Lanka, Subordination, Women